2017
DOI: 10.1038/ismej.2017.190
|View full text |Cite
|
Sign up to set email alerts
|

Phage mobility is a core determinant of phage–bacteria coexistence in biofilms

Abstract: Many bacteria are adapted for attaching to surfaces and for building complex communities, termed biofilms. The biofilm mode of life is predominant in bacterial ecology. So too is the exposure of bacteria to ubiquitous viral pathogens, termed bacteriophages. Although biofilm–phage encounters are likely to be common in nature, little is known about how phages might interact with biofilm-dwelling bacteria. It is also unclear how the ecological dynamics of phages and their hosts depend on the biological and physic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
102
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 103 publications
3
102
0
1
Order By: Relevance
“…For example, our diverging latency time with nutrient depletion means that the phages do not prey on stationary state bacteria, an assumption that is mostly correct but would fail for example for phage T7 preying on Escherichia coli 44 . Note that spatial structure is still relevant in such a case, as shown in protection by biofilm that hinders physical contact of phages to bacteria 30,32,55 . We use a relatively high decay rate for the phage, δ = 0.1 h −1 which is comparable to the larger values reported in the ocean 36 but significantly higher than what is reported in more stable media 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, our diverging latency time with nutrient depletion means that the phages do not prey on stationary state bacteria, an assumption that is mostly correct but would fail for example for phage T7 preying on Escherichia coli 44 . Note that spatial structure is still relevant in such a case, as shown in protection by biofilm that hinders physical contact of phages to bacteria 30,32,55 . We use a relatively high decay rate for the phage, δ = 0.1 h −1 which is comparable to the larger values reported in the ocean 36 but significantly higher than what is reported in more stable media 26 .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that a similar approach of coupling mass-action growth and lattice model was taken in ref. 32 to simulate the phage attack on a biofilm with the spacial resolution of ~ 4 μm. We here consider length scales which are orders of magnitude larger where one lattice site can contain several of microcolonies.…”
mentioning
confidence: 99%
“…A recent study showed that Escherichia coli produces an amyloid fiber network that protects cells in a biofilm individually and reduces phage diffusion (41). Survival in the face of phage can instead occur because the bacteria reduce the expression of their phage receptors (42), or because they slow down growth as nutrients are depleted (40, 43, 44). Our data support a model whereby growth arrest can prevent phage infection (26, 32, 4548).…”
Section: Discussionmentioning
confidence: 99%
“…in protection by biofilm that hinders physical contact of phages to bacteria [25,46]. Also 385 the equations do not consider temperate phages, which would only induce a collapse of 386 order 0.1 to 0.01 (typical recorded lysogeny frequencies [34]).…”
mentioning
confidence: 99%